Research on Strengthening the Education and Training of Grassroots Civil Servants - Dai, Mingjun (Journal of Theory and Practice of Contemporary Education, 2023)
Grass-root civil servants directly face and serve the grass-roots people, undertake the task of stability and development of grass-roots communities and rural areas, and are the specific executors of the Party's and national lines, guidelines and policies. Their quality, ability and style directly determine the strength of the grass-roots government's executive power, the level of efficiency, the quality of the relationship between cadres and the masses, and the success or failure of building a well-off society in an all-round way. It is an effective way to improve the moral cultivation and professional level of grass-roots civil servants to do a good job of education and training for grass-roots civil servants, especially for civil servants in villages and towns, streets and other grass-roots departments. The focus of this paper is to put forward relevant countermeasures and suggestions for the necessity of the education and training of grass-roots civil servants, in order to make a beneficial exploration and attempt for the practical training of grass-roots civil servants.